THE EFFECT OF THE JIGSAW COOPERATIVE LEARNING MODEL ON LEARNING OUTCOMES IN THE COGNITIVE DOMAIN OF CLASS VIII STUDENTS OF SMPN 1 LUBUK ALUNG - Alfatini, Yumna; Lestari, Tuti (Universe, 2025)
The educational process is directed at increasing the mastery of knowledge and skills and developing attitudes and values within the framework of student formation and self-development. Low learning outcomes of students in science lessons are among the educational issues encountered in the field. This is influenced by students' decreased interest in learning in class; there are still many students who are less active and motivated in learning, and the learning model used remains unchanged. Therefore, teachers should use an interesting learning model to create effective, innovative, and fun lessons so that students are more interested in learning science. This study aims to determine the effect of the jigsaw cooperative learning model on learning outcomes in the cognitive domain of students in the digestive system material in class VIII humans at SMPN 1 Lubuk Alung. The type of research used is a quasi-experimental design with a non-equivalent control group design. The experimental class uses a jigsaw cooperative learning model, while the control class uses a conventional learning model with the lecture method. The results of the data analysis showed that the learning outcomes of students in the experimental class were significantly different compared to the control class. The use of the jigsaw-type cooperative learning model has a good influence on improving student learning outcomes. The results of the hypothesis test based on the data obtained in the posttest data research, namely that H1 is accepted and H0 is rejected, are from the posttest value hypothesis through the t test. The data obtained are t count 2,93 and t table 2,00. The data shows tcount > ttable, which means that there is a difference in the average increase in student learning outcomes between the experimental class and the control class. The jigsaw cooperative learning model has an effect on students' cognitive domain learning outcomes in the material of the human digestive system at SMPN 1 Lubuk Alung.